A systematic review of implant materials for facial reconstructive and aesthetic surgery - Kauke-Navarro, Martin; Knoedler, Leonard; Baecher, Helena; Sherwani, Khalil; Knoedler, Samuel; Allam, Omar; Diatta, Fortunay; Alperovich, Michael; Safi, Ali-Farid (Frontiers in Surgery, 2025)
BackgroundAssessing facial plastic surgery techniques is essential for improving patient safety and outcomes through evidence-based practices. Despite the extensive use of facial implants, there is a scarcity of thorough research on their long-term effects and safety profiles.MethodsA systematic review was conducted following PRISMA guidelines, analyzing studies from 1970 to 2024 on various implant materials for facial reconstruction and augmentation. The databases searched for this review included PubMed, Web of Science, Google Scholar, and EMBASE. Inclusion criteria were full-text articles in English, focusing on alloplastic materials for craniofacial skeleton replacement or augmentation.ResultsWe included 117 studies with 4,273 patients and a mean follow-up of 34 months (range: 15 days to 25 years). Of these, 56% focused on reconstruction, 33% on aesthetics, and 10% on both. Patient ages ranged from 6 months to 85 years, with most studies addressing the orbital (29%), chin (22%), and malar (19%) regions. 67% of studies evaluated potential complications and found an overall rate of 4.4%. Nerve injuries (2.1%) and infections (1.0%) were the most frequent issues, with hematoma, implant displacement, and bone resorption rates at 1.4%, 0.59%, and 0.68%, respectively. Patient-specific implants (PSIs) showed promise in reducing complications such as infections, suggesting that customization to patient anatomy may provide benefits. The highest rate of complication-free postoperative recovery was observed with polyethylene facial implants.ConclusionThis review highlights variability in implant performance. The increased use of PSI suggests improved outcomes, warranting further investigation. Standardized outcome reporting and further research are needed to enhance comparability and guide clinical practice.Systematic Review RegistrationPROSPERO, identifier (CRD42024501754).